Pemberdayaan Masyarakat di Desa Pucak dalam Pemanfaatan Tanaman Herbal Sebagai Gel Antiseptik - A. Hasrawati; Iskandar Zulkarnain; Aztriana Aztriana (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Maintaining hand hygiene is one of the most important steps to minimize the spread of disease from viruses and bacteria. But in reality there are still many people who are lazy to do it. In fact, the hands are one of the entrances for germs to enter the body. The use of antiseptics is an effort made to prevent disease transmission other than washing with soap. The practical use of hand sanitizer is a solution to keep hands clean anytime and anywhere. Natural ingredients are one of the right choices in making antiseptics because of the active chemical components that can fight bacteria or viruses, including piper betel leaf and orange peel. The chemical content of piper betel leaf and orange peel has anti-bacterial activity. This service activity aims to provide knowledge about training in making antiseptic gels from herbs, namely with the main ingredients of piper betel leaf and orange peel in partner groups in Pucak village, Bontonompo sub-district, Maros district. The community service activity was carried out in the form of training by providing materials and practices for the use of natural basic ingredients as an effort to make antiseptic gels made from herbs